Medium-term energy outlook for Cyprus and its policy implications - Zachariadis, Theodoros (My University, 2011)
This short paper presents results from an energy forecast model for the Republic of Cyprus. The model was used during years 2010-2011 to assist national authorities in their preparation of the National Renewable Energy Action Plan and the Energy Efficiency Action Plan of Cyprus in line with the requirements of European Union Directives. Major macroeconomic and price assumptions of the model are presented, and results from model application under different assumptions with regard to the evolution of energy efficiency are outlined and discussed. On the basis of these scenarios the paper discusses policy implications for Cyprus regarding the country's compliance with EU energy and climate legislation.
Keywords: Energy demand; Energy efficiency; Forecast